Egyptian Journal of Neurosurgery
Egyptian Journal of Neurosurgery (EJNS), the official publication of the Egyptian Society of Neurological Surgeons, is a peer-reviewed, open access online journal publishing articles in the field of the neurosciences. The journal explores theories and techniques related to the neurosciences and practice of contemporary neurosurgery.  The broad scope of the journal can be extended to those interested in topics from the spine to skull base conditions, rhinology and craniofacial conditions, as well as pediatric oncology, neuro-radiology and traumatology.  The journal welcomes submissions from authors with diverse clinical and scientific interests provided that the article has a relevance to the neurosciences and practice of contemporary neurosurgery, in its widest sense.   The ultimate aim of the journal, is the regional and international coverage and exchange of knowledge in the African continent as well as internationally, exposing the available experience and vast service being delivered to standardise the practice of neurosurgery, improve the level of performance and enhance scientific research in the field.